The use of implementation strategies to promote the uptake of psychological therapies among people with multiple sclerosis: A scoping review protocol - Ashvene Sureshkumar; Robert Simpson; Mark Bayley; Monika Kastner; Jillian Scandiffio; Emilia Main; Claire Zhang; Harzaan Gnanakaran; Joshua Wijeratne; Alesha Saxena; Sarah Munce (PLoS ONE, 2025)
Objective This paper aims to standardize a scoping review protocol for completion of a scoping review. The proposed scoping review aims to: 1) determine the extent of the literature on which implementation strategies have been used to develop, deliver, and sustain psychological interventions for people with multiple sclerosis (PwMS) and 2) investigate how equity, diversity, inclusion and accessibility considerations are embedded within these implementation strategies and psychological interventions more broadly. Introduction People with multiple sclerosis experience high levels of stress, anxiety and depression. Psychological interventions, such as mindfulness-based interventions have been shown to be effective in managing these symptoms, yet their implementation in clinical practice is underexplored. Investigating the implementation of psychological interventions can help contextualize the efficacy and impact of these programs for PwMS. This proposed review aims to fill this knowledge gap by determining which implementation strategies have been used to develop and deliver psychological interventions for PwMS. Methods This scoping review will follow the Joanna Briggs Institute (JBI) methodology and reporting will follow the Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for scoping review (PRISMA-ScR). The search will be conducted across MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and PsychInfo (Scopus). Two reviewers will independently conduct screening and data extraction in duplicate, with any disagreements resolved through discussion and involvement of a third reviewer. Data extraction will be guided by the JBI template. Quantitative data will be reported descriptively, and a conventional content analysis will be undertaken for qualitative data. Inclusion criteria This scoping review will include studies globally published in peer-reviewed academic journals in English involving PwMS that report on implementation strategies for live, professional-led psychological interventions. Pharmacological studies or studies focusing only on effectiveness of psychological interventions will be excluded.